2019
DOI: 10.3390/foods8110540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Maltase and Sucrase Inhibitory Constituents from Rhodiola crenulata

Abstract: The inhibitory properties of epicatechin-(4β,8)-epicatechingallate (B2-3’-O-gallate), epicatechin gallate (ECG), and epicatechin (EC) isolated from Rhodiola crenulata toward maltase and sucrase were investigated. The half-maximal inhibitory concentration (IC50) values for maltase were as follows: B2-3’-O-gallate (1.73 ± 1.37 μM), ECG (3.64 ± 2.99 μM), and EC (6.25 ± 1.84 μM). Inhibition kinetic assays revealed the inhibition constants (Ki) of the mixed-competitive inhibitors of maltase, as follows: B2-3’-O-gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The MANE extract displays significant maltase and sucrase inhibition and is one of the most effective reported to date. The observed variation in IC 50 reported in the literature could be linked to the use of specific experimental conditions, seaweed species, extraction procedures, extract composition and bioactive component physicochemical properties ( 45 , 49 , 50 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The MANE extract displays significant maltase and sucrase inhibition and is one of the most effective reported to date. The observed variation in IC 50 reported in the literature could be linked to the use of specific experimental conditions, seaweed species, extraction procedures, extract composition and bioactive component physicochemical properties ( 45 , 49 , 50 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The sucrase inhibition assay was performed according to the method outlined by Honda et al with some modifications [33]. In brief, 10 µL of enzyme solution (100 U/mL) and 30 µL of test sample solution with appropriate concentration (dissolved in distilled water) were added into the 96-well plates, and were incubated for 10 min at 37 • C. The reaction was conducted by addition of 100 µL of sucrose solution (60 mM, dissolved in 0.1 M phosphate buffer solution).…”
Section: Sucrase Inhibition Assaymentioning
confidence: 99%
“…Rhodiola is inclined to grow in mountainous areas of low temperature such as precipices, tundra, riverbanks, and rock ledges in the northern hemisphere including Asia, North and Central Europe, and North America [3]. It consists of more than 100 species, of which about 20 species are used as traditional medicines, including Rhodiola rosea (R. rosea), Rhodiola crenulata (R. crenulata), Rhodiola sacra (R. sacra), and Rhodiola kirilovii [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…crenulata ), Rhodiola sacra ( R . sacra ), and Rhodiola kirilovii [ 4 , 5 ]. Growing studies have demonstrated that Rhodiola possesses varieties of bioactivities such as antistress, antifatigue, antioxidant, antitumor, anti‐inflammation, antiaging, antiradiation, and immunomodulatory [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%